Hedging late frost risk with American binary options: An application to grape cultivation in Argentina - Cortina, Elsa Aurora (2012)
The purpose of this paper is to model and to value a temperature derivative to hedge late frost risk in grape cultivation. Starting from historical data, we propose a continuous stochastic model to describe the minimum temperature behavior. We define an American binary option to hedge late frost risk, and present a numerical application to grape cultivation.